The post-colonial studies reader - Ashcroft, Bill; Griffiths, Gareth; Tiffin, Helen (Routledge, 1995)
The Post-Colonial Studies Reader is the most comprehensive selection of key texts in post-colonial theory and criticism yet compiled. This collection covers a huge range of topics, featuring nearly ninety of the discipline's most widely read works. The Reader's 90 extracts are designed to introduce the major issues and debates in the field of post-colonial literary studies. This field itself, however, has become so varied that no collection of readings could encompass every voice which is now giving itself the name "post-colonial." The editors, in order to avoid a volume which is simply a critical canon, have selected works representing arguments with which they do not necessarily agree, but rather which above all stimulate discussion, thought and further exploration. Post-colonial "theory" has occurred in all societies into which the imperial force of Europe has intruded, though not always in the official form of theoretical text. Like the description of any other field the term has come to mean many things, but this volume hinges on one incontestable phenomenon: the "historical fact"of colonialism, and the palpable consequences to which this phenomenon gave rise. The topic involves talk about experience of various kinds: migration, slavery, suppression, resistance, representation, difference, race, gender, place, and reaction to the European influence, and about the fundamental experiences of speaking and writing by which all these come into being. In compiling this reader, the editors have sought to stimulate people to ask: "How might a genuinely post-colonial literary enterprise proceed?" The fourteen sections include: Issues and Debates; Universality and Difference; Textual Representation and Resistance; Postmodernism and Post-Colonialism; Nationalism; Hybridity; Ethnicity and Indigenity; Feminism and Post-Colonialism; Language; The Body and Performance; History; Place; Education; and Production and Consumption. Contributors include many of the leading post-colonial theorists and critics–such as Franz Fanon, Chinua Achebe, Gayatri Chakravorty Spivak, Ngugi wa Thiong'o, Homi Bhabba, Derek Walcott, Edward Said, and Trinh T. Minh-ha–in addition to a number of the discourse's newer voices. The Post-Colonial Studies Reader will prove an authoritative compilation, representing an invaluable contribution to the study of post-colonial theory and criticism.
Keywords: 1900-1999; 1990-1999; approches et analyses; arts; discipline; fem1000; féminisme décolonial; histoire et politique; littérature; premier cycle; périodes historiques; thématiques; études culturelles; études littéraires

The apparitional lesbian: Female homosexuality and modern culture - Castle, Terry (Columbia University Press, 1995)
In essays on literary images of lesbianism from Defoe and Diderot to Virginia Woolf and Djuna Barnes, on the homosexual reputation of Marie Antoinette, on the lesbian writings of Anne Lister, Sylvia Townsend Warner, and Janet Flanner, and on Henry James's The Bostonians, Castle shows how a lesbian presence can be identified in the literature, history, and culture of the past three centuries.
Keywords: approches et analyses; arts; discipline; identités LGBTQIA2+; lesbianisme; études littéraires

Professions of desire lesbian and gay studies in literature - Haggerty, George E.; Zimmerman, Bonnie (Modern language Association of America, 1995)
Premier recueil d'essais abordant les questions concernant les études lesbiennes et gays dans les classes de premier cycle, Professions du désir mettra au défi les enseignant.e.s et les étudiant.e.s en littérature avec de nouveaux matériaux, de nouvelles approches et de nouvelles idées. Professions du désir comprend des exemples d'analyses critiques lesbiennes et gays et des discussions réfléchies sur ce que signifie être lesbienne, gay ou queer en classe.
Keywords: arts; discipline; identités LGBTQIA2+; pédagogie; thématiques; études littéraires

La femme créatrice est l'homme le plus seul au monde : roman familial et problèmes de la création au féminin dans La montagne secrète de Gabrielle Roy - Lamarre, Sylvie (Université du Québec à Montréal, 1995)
Keywords: 1900-1999; 1960-1969; IREF; amériques; arts; canada; discipline; mémoires/thèses; périodes historiques; régions géographiques; thématiques; écriture des femmes*; études littéraires

Romance revisited - Pearce, Lynne; Stacey, Jackie (New York University Press, 1995)
Après des décennies de féminisme et de déconstruction, la romance reste fermement ancrée comme une préoccupation centrale dans la vie de la plupart des femmes. Les taux de divorce montent en flèche, la famille traditionnelle est remise en question de toutes parts et pourtant la romance semble indestructible. En termes de représentation culturelle, la popularité de la romance semble également incontestée. La fiction populaire, le cinéma hollywoodien, les feuilletons télévisés et les médias en général affichent tous un appétit apparemment sans limite pour les sujets romantiques. Les pièges de la romance classique – mariages blancs, chansons d’amour, Saint-Valentin – sont plus que jamais commercialement viables. Dans cette anthologie d'essais originaux, la romance est revisitée sous un large éventail de perspectives, non seulement dans la fiction et le cinéma, mais dans toute une gamme de phénomènes culturels. Les essais couvrent des sujets tels que la Saint-Valentin, les relations interraciales, les visions érotiques médiévales et la fiction romantique moderne, la relation entre la poétesse lesbienne HD et Bryher, la blancheur omniprésente du désir romantique, l'érotisme lesbien à l'ère du SIDA et la romance publique de Charles et Diane.
Keywords: anthologie; approches et analyses; arts; classisme; discipline; histoire et politique; outils; ouvrages de références; patriarcat; racisme; romance; sexisme; sexualité; systèmes d'oppression; thématiques; études culturelles; études littéraires

Identités en devenir et famille subvertie dans l'oeuvre de Jovette Marchessault - Poirier, Martin (Université du Québec à Montréal, 1995)
Ce mémoire présente une analyse du roman Des cailloux blancs pour les forêts obscures (Montréal: Leméac, 1987) de Jovette Marchessault. L'approche théorique utilisée est avant tout inspirée du travail de Marianne Hirsch (The Mother/Daughter Plot, 1989) qui revoit la notion de «roman familial» de Freud d'un point de vue féministe. Les réflexions de Luce Irigaray et de Claire Lejeune à propos de la notion identitaire et de la constitution de famille servent également à l'analyse. La question principale qui guide l'ensemble des quatre chapitres du mémoire est la suivante: en quoi les remises en question identitaires des personnages féminins et masculins arrivent-elles à transformer les structures de la famille patriarcale et les caractéristiques du roman familial traditionnel?
Keywords: amériques; approches et analyses; arts; discipline; famille; mémoires/thèses; patriarcat; québec; régions géographiques; systèmes d'oppression; études littéraires